Is the intention to use public transport for different travel purposes determined by different factors? - Zailani, S.; Iranmanesh, M.; Masron, T.A.; Chan, T.H. (Elsevier, 2016)
The objective of this study was to examine the psychological predictors of the intention to use public transport for three travel purposes: work or study, shopping, and leisure. An expanded version of the theory of planned behaviour (TPB) which contains overall image and past behaviour is used. Data were gathered through the survey of 392 residents living in the central parts of Kuala Lumpur in Malaysia. These data were analysed using the partial least squares technique. The results indicate that attitude and perceived behavioural control are significant predictors of the intention to use public transportation for various purposes. Further, they explain between 34.6% and 49.8% of the intention variance. By adding the overall image and past behaviour to the original predictors in the TPB, the explained variance, with regard to work or study, shopping, and leisure purposes, increased by 5.6%, 5.1%, and 6.8%, respectively.